THE CONTRIBUTION OF BIO-POLYMERS TO PHARMACEUTICAL INDUSTRY 2. EVALUATION OF SAS-LUB, A NEW BIFUNCTIONAL TABLETTING EXCIPIENT - Al-muaikel, Nayef S (European Scientific Journal, ESJ, 2014)
SAS-Lub, a new bi-functional excipient co-processed from microcrystalline cellulose and olive oil was evaluated as a lubricant against magnesium stearate, MS, in a model direct compression tablet formulation compressed from micro-crystalline cellulose, MCC at a fixed compressional pressure. The result showed SAS-Lub decreased the plastic deformation of MCC and generated a higher decompression index, kc which was determined from: (1-D) = (1-D)o ekc .C where D, Do and C stand for the relative densities of a tablet batch before and after lubrication and the concentration of the added lubricant material, respectively. Unfortunately, SAS-Lub imported a higher adverse effect on the tablet tensile strength and friability. Unlike MS, SAS-Lub showed a disintegration activity. The disintegration rate constant, kd, was fairly correlate to C in a tablet batch by the relation: kd = kO d ekx.C where kO d and kx stand for the disintegration rate constant of the tablet batch before lubrication and the disintegration inducing index, DII, respectively.